Sustainable supplier evaluation under due diligence acts - Kraft, Sarah Katharina; Quayson, Matthew; Kellner, Florian (Frontiers in Sustainability, 2025)
The enactment of due diligence legislation, such as the German Act on Corporate Due Diligence Obligations in Supply Chains, in German Lieferkettensorgfaltspflichtengesetz (LkSG), is reshaping global supply chain management by compelling companies to tackle heightened human rights and environmental risks in their supply chain. This study addresses the need for a comprehensive sustainability supplier evaluation framework by employing a systematic literature review with an expert survey of practitioners from German companies subject to LkSG. This methodology aligns academic findings with real-world practice and legal requirements, enriching the literature with practical insights. The results reveal that business practice prioritizes economic and social dimensions, whereas the literature focuses on economic and environmental dimensions. Although the most relevant economic and environmental criteria are consistent across both domains, the key social criteria show a notable misalignment. Managers can utilize the most relevant sustainability supplier evaluation criteria identified in this study to promote sustainable supply chains and ensure compliance with due diligence requirements. This research also highlights the high relevance of human rights as a social criterion, a dimension that has been historically under-recognized or implicitly addressed in the literature.